Blockade of receptors of advanced glycation end products ameliorates diabetic osteogenesis of adipose‐derived stem cells through DNA methylation and Wnt signalling pathway. (16th July 2018) - Zhang, Maorui; Li, Yong; Rao, Pengcheng; Huang, Kui; Luo, Daowen; Cai, Xiaoxiao; Xiao, Jingang
Abstract: Objectives: Diabetes mellitus‐related osteoporosis is caused by the imbalance between bone absorption and bone formation. Advanced glycation end products (AGEs) are considered a cause of diabetic osteoporosis. Although adipose‐derived stem cells (ASCs) are promising adult stem cells in bone tissue regeneration, the ability of osteogenesis of ASCs in diabetic environment needs to explore. This study aimed to investigate the influence of AGEs on the osteogenic potential of ASCs and to explore the signalling pathways involved in its effect. Materials and methods: ASCs were isolated from inguinal fat and cultured in osteogenic media with or without AGEs and FPS‐ZM1, an inhibitor of receptor for AGEs (RAGE). Alizarin red‐S, Oil Red‐O and Alcian blue staining were used to confirm osteogenic, adipogenic and chondrogenic potential of ASCs, respectively. Immunofluorescence, western blotting and real‐time PCR were used to measure changes in markers of osteogenic differentiation, DNA methylation and Wnt signalling. Results: The multipotentiality of ASCs was confirmed. Treated with AGEs, OPN and RUNX2 expressions of ASCs were reduced and there was a noticeable loss of mineralization, concomitant with an increase in the expression of RAGE, 5‐MC, DNMT1 and DNMT3a. AGEs treatment also led to a loss of Wnt signalling pathway markers, including β‐Catenin and LEF1, with an increase in GSK‐3β. Treatment with the RAGE inhibitor, FPS‐ZM1, rescued AGEs‐induced loss of osteogenic potential, modulated DNA methylation and upregulated Wnt signalling in ASCs. Conclusions: Our results demonstrate that AGEs‐RAGE signalling inhibits the osteogenic potential of ASCs under osteoinductive conditions by modulating DNA methylation and Wnt signalling. FPS‐ZM1 can rescue the negative effects of AGEs and provide a possible treatment for bone tissue regeneration in patients with diabetic osteoporosis.